2019
DOI: 10.1002/advs.201901166
|View full text |Cite
|
Sign up to set email alerts
|

Magnesium Regulates Endothelial Barrier Functions through TRPM7, MagT1, and S1P1

Abstract: Mg2+‐deficiency is linked to hypertension, Alzheimer's disease, stroke, migraine headaches, cardiovascular diseases, and diabetes, etc., but its exact role in these pathophysiological conditions remains elusive. Mg2+ can regulate vascular functions, yet the mechanistic insight remains ill‐defined. Data show that extracellular Mg2+ enters endothelium mainly through the TRPM7 channel and MagT1 transporter. Mg2+ can act as an antagonist to reduce Ca2+ signaling in endothelium. Mg2+ also reduces the intracellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 68 publications
1
71
0
Order By: Relevance
“…The reason may relate to the role of magnesium in neuroprotection and hemostasis. Rt-PA can cause post-stroke HT by inducing oxidative stress that further compromise the BBB ( 3 ), and magnesium-deficiency would lead to enhanced permeability of the cerebrovascular endothelial barrier as proved in mouse models ( 7 ). Intraperitoneal injections with magnesium sulfate in normal mice reduced histamine-induced endothelial hyper-permeability mainly by suppressing oxidative stress and inflammatory responses, while up-regulating endothelial barrier-stabilizing mediators such as cyclic adenosine monophosphate ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reason may relate to the role of magnesium in neuroprotection and hemostasis. Rt-PA can cause post-stroke HT by inducing oxidative stress that further compromise the BBB ( 3 ), and magnesium-deficiency would lead to enhanced permeability of the cerebrovascular endothelial barrier as proved in mouse models ( 7 ). Intraperitoneal injections with magnesium sulfate in normal mice reduced histamine-induced endothelial hyper-permeability mainly by suppressing oxidative stress and inflammatory responses, while up-regulating endothelial barrier-stabilizing mediators such as cyclic adenosine monophosphate ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rt-PA can cause post-stroke HT by inducing oxidative stress that further compromise the BBB ( 3 ), and magnesium-deficiency would lead to enhanced permeability of the cerebrovascular endothelial barrier as proved in mouse models ( 7 ). Intraperitoneal injections with magnesium sulfate in normal mice reduced histamine-induced endothelial hyper-permeability mainly by suppressing oxidative stress and inflammatory responses, while up-regulating endothelial barrier-stabilizing mediators such as cyclic adenosine monophosphate ( 7 ). In rats subjected to transient focal cerebral ischemia, magnesium showed the ability to protect BBB integrity by increasing the activity of anti-oxidant enzymes and decreasing lipid peroxide levels ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Human microvascular endothelial cells (HMECs) cultured with a lower concentration of Mg 2+ resulted in impaired proliferation, increasing the number of cells in the gap (G 0 –G 1 ) phase of the cell cycle and downregulation of TRPM7, whereas silencing of TRPM7 showed similar results in this model [ 38 ]. In an experimental model, TRPM7 and MagT1 were seen as relevant for Mg 2+ homeostasis in endothelial cells [ 39 ]. In this same study, the deficiency of Mg 2+ increased the levels of reactive oxygen species (ROS), prostaglandin E2 (PGE2), TNF-α, and IL-1β, and altered the messenger RNA (mRNA) expression of ICAM-1 and VCAM-1 .…”
Section: The Role Of Mg 2+ In Hematopoiesismentioning
confidence: 99%
“…In addition, less viability and cell proliferation were observed during Mg 2+ deficiency, along with changes in endothelial permeability, and a possible role in regulating the integrity of the endothelial barrier through the sphingosine-1-phosphate receptor 1 (S1P1)–Ras-related C3 botulinum toxin substrate 1 (Rac1) pathway. On the other hand, the authors found that treatment with Mg 2+ was able to reestablish endothelial homeostasis [ 39 ] ( Figure 1 ).…”
Section: The Role Of Mg 2+ In Hematopoiesismentioning
confidence: 99%